2016
DOI: 10.1016/j.jpag.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Urban Adolescents' and Young Adults' Decision-Making Process around Selection of Intrauterine Contraception

Abstract: Study Objective To examine adolescent and young adults’ priorities, values and preferences affecting the choice to use intrauterine contraception (IUC). Design and participants Qualitative exploratory semi-structured interviews with 27 females 16–25 years old on the day of their IUC insertion. Analysis was done using a modified grounded theory approach. Setting Outpatient adolescent medicine clinic located within an academic children’s hospital in the Bronx, New York Results We identified four broad fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 22 publications
0
44
0
1
Order By: Relevance
“…Little research has investigated what young women desire from contraceptive counseling. The limited available research indicates that young women prefer patient-centered approaches and counseling tailored to address their specific contraceptive needs (Brown, Auerswald, Eyre, Deardorff, & Dehlendorf, 2013;Rubin, Felsher, Korich, & Jacobs, 2016). Across age groups, women report that autonomy in their contraceptive decisions is particularly important, even more so than for decisions about other aspects of their health care (Dehlendorf, Diedrich, Drey, Postone, & Steinauer, 2010).…”
mentioning
confidence: 99%
“…Little research has investigated what young women desire from contraceptive counseling. The limited available research indicates that young women prefer patient-centered approaches and counseling tailored to address their specific contraceptive needs (Brown, Auerswald, Eyre, Deardorff, & Dehlendorf, 2013;Rubin, Felsher, Korich, & Jacobs, 2016). Across age groups, women report that autonomy in their contraceptive decisions is particularly important, even more so than for decisions about other aspects of their health care (Dehlendorf, Diedrich, Drey, Postone, & Steinauer, 2010).…”
mentioning
confidence: 99%
“…The benefits of the copper IUCD for young women include its affordable price, its non‐binding feature that does not require the user to do anything once it is inserted, and its fewer adverse effects as compared with hormonal methods (i.e., pills and injectables) . It was previously reported that quality counseling may increase the number of adolescents and young women who choose the IUCD method because it is a good fit for them …”
Section: Discussionmentioning
confidence: 99%
“…20,21 It was previously reported that quality counseling may increase the number of adolescents and young women who choose the IUCD method because it is a good fit for them. 22 The strengths of the present study include its substantial sample size and its focus on primary health facilities, where there is most need for family planning services. However, some limitations must be noted including the small number of health facilities and a lack of qualitative T A B L E 2 Uptake of family planning methods at the two health facilities before and during the SOGOB intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Flyers and consent forms contained information about participant inclusion criteria, and researchers verbally confirmed with participants that they will have or have had birth control conversations with a provider. In the first five focus groups, we stratified women by age (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and race/ethnicity (White non-Hispanic, African American non-Hispanic, and Hispanic [White, African American, other]) ( Table 1) to examine differences within a community that faces racial and ethnic disparities in sexual and reproductive health such as teen pregnancy and poor birth outcomes [33]. Women self-identified age, race, and ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown the important role of parental figures in influencing adolescent sexual health behaviors [15,16] and parent-based sexual education successfully leading to increased communication within the parent-child dyad [17]. Not surprisingly, mothers reported the importance of maternal-adolescent conversations about contraception [18] and were identified by young women as a key player in the role of contraceptive method choice, influencing intrauterine contraception uptake [19]. Moreover, evidence has shown that positive maternal relationships were a protective factor against inconsistent condom use [20].…”
Section: Introductionmentioning
confidence: 99%